2007
DOI: 10.1098/rstb.2007.2217
|View full text |Cite
|
Sign up to set email alerts
|

Water oxidation chemistry of photosystem II

Abstract: Photosystem II (PSII ) uses light energy to split water into protons, electrons and O 2 . In this reaction, nature has solved the difficult chemical problem of efficient four-electron oxidation of water to yield O 2 without significant amounts of reactive intermediate species such as superoxide, hydrogen peroxide and hydroxyl radicals. In order to use nature's solution for the design of artificial catalysts that split water, it is important to understand the mechanism of the reaction. The recently published X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
156
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(160 citation statements)
references
References 62 publications
2
156
0
Order By: Relevance
“…Thus, complex 1 approaches both the geometric and electronic structure of the OEC and provides a foundation for ongoing efforts to extend this work to additional relevant models of the OEC. We are currently exploring ligand variation in 1 to impose structural perturbations that might also alter the ground state by altering the J∕J 0 ratio, the replacement of the external Ca with Mn, and assessing reactivity as a basis for developing biomimetic water oxidation activity (35)(36)(37)(38)(39). The attainment of 1 is an important breakthrough that provides a valuable foundation for future work in various directions and should permit a deeper level of insights into the nature and mode of action of this crucial biological site.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, complex 1 approaches both the geometric and electronic structure of the OEC and provides a foundation for ongoing efforts to extend this work to additional relevant models of the OEC. We are currently exploring ligand variation in 1 to impose structural perturbations that might also alter the ground state by altering the J∕J 0 ratio, the replacement of the external Ca with Mn, and assessing reactivity as a basis for developing biomimetic water oxidation activity (35)(36)(37)(38)(39). The attainment of 1 is an important breakthrough that provides a valuable foundation for future work in various directions and should permit a deeper level of insights into the nature and mode of action of this crucial biological site.…”
Section: Discussionmentioning
confidence: 99%
“…Substrate water molecules bind to the cluster and, upon oxidation, are coupled to produce dioxygen and 4 eq of protons. There is agreement that formation of the O-O bond occurs in the highest oxidized state of the Mn 4 CaO 5 cluster (S 4 ), after which the cluster reverts to the most reduced state, S 0 (1)(2)(3)(4)(5)(6)(8)(9)(10). The transient S 4 state has eluded detection, making it difficult to experimentally probe the structural and physical requirements necessary to promote dioxygen production.…”
mentioning
confidence: 99%
“…Nevertheless, density function calculations (Lundberg and Siegbahn 2004;Sproviero et al 2006Sproviero et al , 2007Batista et al 2008) and chemical synthesis of mixed Mn/Ca complexes (Mishra et al 2005), shown more recently by Kanady et al (2011) and Mukherjee et al (2012), suggested that such an organization was chemically feasible despite there being no known similar structure in biology at the time. Moreover, the model provided an important basis for its further refinement by quantum mechanical calculations and for developing detailed mechanisms for the water-splitting reaction leading to dioxygen formation Brudvig 2004, 2006;Siegbahn 2006Siegbahn , 2008Siegbahn , 2009Siegbahn , 2012Brudvig 2008;Dau et al 2008). On the basis of this organization of the metal ions, the Mn 3 CaO 4 cubane had four protein side chains as potential ligands: D1Asp342, D1Glu189, D1His332, and CP43Glu354.…”
Section: Cofactorsmentioning
confidence: 99%
“…The Mn ion outside the cubane (Mn4) is adjacent to the Ca 2þ , and their positioning toward the side chains of several key amino acids, including the redox-active Y Z , suggests that they provide the "catalytic" surface for binding the two substrate W molecules and their subsequent oxidation. One well-championed mechanism (Messinger et al 1995;Pecoraro et al 1998;Brudvig 2004, 2006;Brudvig 2008) suggests that the substrate water, associated with Mn4, is deprotonated during the S-state cycle and converted to a highly electrophilic oxo (see Fig. 5A).…”
Section: Mechanism Of Water Oxidationmentioning
confidence: 99%